Kultivasi Mikroalga Chlorella sp. Secara Fed-Batch Menggunakan Limbah Cair Tahu Untuk Produksi Lipid - Sri Rezeki Muria; Fikri Miftahul Shiddiq; Irma Damayanti; Indra Purnama (Jurusan Teknik Kimia, Fakultas Teknik, UNRI, 2023)
Microalga is single cell organism that can live by photosynthesize resulting biomass and other secondary product such as protein, carbohydrate, and lipid by utilizing nutrients in wastewater. This study aims to get the data about the effect of additions of tofu liquid waste to the growth and increase of lipid content in the microalga that cultivated in tofu liquid waste media. Microalga were cultivated by variations in tofu liquid waste adding. The variations are 0,45 liter in every day, 0,9 liter in every two days, and 1,35 liter in every three days. Microalga growth were measured by an object glass, the amount of cell density in every square field calculated using tomacytometer with hand counter where observed under optical microscope. Total lipid content were gained by employ Bligh-dyer methode. The results of this study show the highest specific grow rate of Chlorella sp is 0,08692/day accounted from tofu liquid waste addition in every three days. The highest lipid content is 40,88 % which gained from tofu liquid waste addition in every day. Under unfavourable condition microalga will accumulate more lipid so that increase it lipid content. The highest chemical oxygen demand (COD) removal is 575 mg/mL.